COVID-19 Related Knowledge, Attitude, Practice Evaluation among Indian Dental Patients: A Cross-Sectional Survey - Deeksha Karkada; Shashidhar Acharya; Prajna P. Nayak (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the awareness about COVID-19 among dental patients and determine the association between COVID-19 awareness and perceived stress among dental patients. Material and Methods: A self-administered knowledge, attitude and practices (KAP) questionnaire and perceived stress scale (PSS) were employed to assess the knowledge and attitude among dental patients visiting the outpatient department. A p-value of ≤ 0.05 was considered statistically significant. An independent t-test was used to compare the KAP and PSS scores based on age, gender, occupation and the responses to unscorable questions. Spearman's correlation was employed to assess the association between KAP and PSS scores. Results: The older participants (mean KAP score = 16±2.2), the participants who answered that the Coronavirus outbreak changed their daily routine (mean KAP score = 15.8±2.2) and the participants who answered that they changed their plans due to the Coronavirus outbreak (mean KAP score = 16±2.14) had significantly higher KAP scores when compared to their respective counterparts. The Spearman's correlation value of -0.45 suggested a moderate negative association between the KAP and PSS scores, but this correlation was not statistically significant. Conclusion: The participants had a moderate to good level of knowledge related to COVID-19 and were positive in their approach and outlook on overcoming the pandemic.